Perancangan Sistem AZIS (Akuntansi Zakat, Infaq, dan Sedekah) pada Organisasi Pengelola Zakat dalam Menghasilkan Laporan Keuangan - Lathifa, Nurul (Akuntansi: Jurnal Akuntansi Integratif, 2019)
Zakat is a treasure that must be released by any Muslim in accordance with the provisions of sharia to be given to those who deserve it (mustahiq). The law of zakat is obligatory (fard) upon every Muslim who has fulfilled certain conditions. The potential of zakat in Indonesia so many, but the management of zakat that Zakat Organization do, is not optimal. The financial statements are produced still different. Zakat Organization is required a good accounting information system to produce reliable and accurate financial reports. Therefore, using descriptive qualitative case study approach, researchers try to apply PSAK No.109 in the process of preparing financial statements zakat and infaq of Zakat Organization with design an accounting information system includes the structural design of the accounting process that starts from the identification and grouping transaction, accounting policies, chart of accounts are used, transaction journals, ledgers. So that in the end will produce financial statements a accordance with PSAK No. 109 which consists of balance sheet, statement of changes in funds, statement of changes in assets under management, and cash flows.